2014
DOI: 10.3892/ol.2014.1925
|View full text |Cite
|
Sign up to set email alerts
|

Primary anorectal malignant melanoma treated with neoadjuvant chemoradiotherapy and sphincter-sparing surgery: A case report

Abstract: Primary anorectal (PA) malignant melanoma (MM) is a rare disease associated with a high mortality rate. The most appropriate treatment strategy for PAMM remains controversial. A 55-year-old female patient, who was misdiagnosed with locally advanced rectal carcinoma, was treated with preoperative radiotherapy and concurrent oral capecitabine. During the therapy, grade 1 leukopenia occurred, however, there was no interruption to treatment. Following chemoradiotherapy, a computer tomography scan identified that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Ballo et al 19 reported a 5-year local and regional nodal control with rates of 74% and 84%, respectively, and Kelly et al 20 achieved a 5-year local control rate of 82%. Neoadjuvant chemo-irradiation (CRT) was performed in order to achieve a pathological response, a negative margins excision and render a sphincter preservation feasible 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Ballo et al 19 reported a 5-year local and regional nodal control with rates of 74% and 84%, respectively, and Kelly et al 20 achieved a 5-year local control rate of 82%. Neoadjuvant chemo-irradiation (CRT) was performed in order to achieve a pathological response, a negative margins excision and render a sphincter preservation feasible 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…1-3 Adjuvant chemotherapy, radiotherapy or immunotherapy as well as neoadjuvant chemoradiotherapy or exclusive chemotherapy have a limited role. [1][2][3][4] Dear Editor,…”
Section: Anorectal Melanoma: a Rare Aggressive Type Of Melanomamentioning
confidence: 99%